2016
DOI: 10.2196/jmir.5056
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Phone App Intervention Targeting Fruit and Vegetable Consumption: The Efficacy of Textual and Auditory Tailored Health Information Tested in a Randomized Controlled Trial

Abstract: BackgroundMobile phone apps are increasingly used to deliver health interventions, which provide the opportunity to present health information via different communication modes. However, scientific evidence regarding the effects of such health apps is scarce.ObjectiveIn a randomized controlled trial, we tested the efficacy of a 6-month intervention delivered via a mobile phone app that communicated either textual or auditory tailored health information aimed at stimulating fruit and vegetable intake. A control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(86 citation statements)
references
References 54 publications
3
78
0
5
Order By: Relevance
“…Data collection and management tools are often a means to change health behavior [15]. In this study, dozens of tools were found ( Table 2).…”
Section: Discussionmentioning
confidence: 91%
“…Data collection and management tools are often a means to change health behavior [15]. In this study, dozens of tools were found ( Table 2).…”
Section: Discussionmentioning
confidence: 91%
“…Twelve studies were conducted in North America [3546], seven studies in Australia/New Zealand [2932, 4751], seven studies in Europe [33, 34, 5257], and one study in the Middle-East [58]. Most studies were randomised controlled trials ( n  = 19) with 2-group [29, 31, 35, 40, 4346, 48, 50, 5255, 58] or 3-group [33, 34, 42, 47, 56, 57] study designs.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were randomised controlled trials ( n  = 19) with 2-group [29, 31, 35, 40, 4346, 48, 50, 5255, 58] or 3-group [33, 34, 42, 47, 56, 57] study designs. The remaining studies were controlled trials ( n  = 3) [33, 37, 49], randomised trials ( n  = 1) [39] or pre-post studies ( n  = 4) [36, 38, 41].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations